2012
DOI: 10.1111/j.1365-2559.2011.04110.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of the microRNA processing enzyme Dicer is a prognostic factor in human colorectal cancer

Abstract: Dicer deregulation is linked significantly to adverse disease state and decreased overall survival in colorectal cancer. Our data suggest that reduced Dicer expression might contribute to tumour progression in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…We have demonstrated significant correlations between the DICER1 mRNA and tumor size, depth of invasion, lymph node metastasis, lymphatic invasion and Dukes' stage. Using the IHC method, Faggad et al (23) reported that the DICER1 protein expression in CRC tissues showed a significant correlation with tumor grade, lymph node metastasis, localization of tumor and tumor stage, thereby partially supporting our findings. We also evaluated the prognostic value of DICER1 mRNA in CRC tissues.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 79%
See 2 more Smart Citations
“…We have demonstrated significant correlations between the DICER1 mRNA and tumor size, depth of invasion, lymph node metastasis, lymphatic invasion and Dukes' stage. Using the IHC method, Faggad et al (23) reported that the DICER1 protein expression in CRC tissues showed a significant correlation with tumor grade, lymph node metastasis, localization of tumor and tumor stage, thereby partially supporting our findings. We also evaluated the prognostic value of DICER1 mRNA in CRC tissues.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 79%
“…By contrast, Faggad et al (23) reported that the downregulation of DICER1 is a prognostic factor in CRC patients with WHO stage I, II, III and IV. These studies examined the DICER1 protein levels of tissue microarrays (TMA) using IHC staining.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the upregulated expression of Dicer in serous ovarian carcinoma is associated with advanced tumor stages (25) and its downregulated expression in breast cancer is associated with cancer progression and recurrence (26). Particularly in CRC, previous studies have identified that dysregulation of the miRNA machinery may be involved in carcinogenesis (10,14,16,27,28). Drosha mRNA levels were not identified to be significantly associated with tumor stages (10).…”
Section: Discussionmentioning
confidence: 71%
“…Global repression of miRNAs in human cancers has been observed in previous studies (11,12) and has been suggested to result from defective biogenesis machinery. Dysregulation of Dicer is of great interest because, similarly to the suppression of miRNA, downregulation of Dicer has been widely observed in many types of human tumors and Dicer has been shown to function as a tumor suppressor (12)(13)(14)(15)(16)(17). Suppression of Dicer expression was found to dramatically enhance cancer metastasis through miR-200 miRNA (15,18).…”
Section: Introductionmentioning
confidence: 99%